Pre-exercise carbohydrate meal and endurance running capacity when carbohydrates are ingested during exercise - Chryssanthopoulos, C.; Williams, C. (International Journal of Sports Medicine, 1997)
This study examined whether combining a pre-exercise carbohydrate meal with the ingestion of a carbohydrate-electrolyte solution during exercise is better in improving endurance running capacity than a carbohydrate-electrolyte solution alone. Ten men completed three treadmill runs at 70% VO2max to exhaustion. They consumed 1.) a carbohydrate meal three hours before exercise and a carbohydrate-electrolyte solution during exercise (M + C), or 2.) a liquid placebo three hours before exercise and the carbohydrate-electrolyte solution during exercise (P + C), or 3.) a placebo three hours before exercise and placebo during exercise (P + P). When the meal was consumed (M + C) serum insulin concentrations were higher at the start of exercise, and carbohydrate oxidation rates were higher during the first 60 min of exercise compared with the values found in the P + C and P + P trials (p < 0.01). Exercise time was longer in the M + C (147.4+/-9.6 min) compared with the P + C (125.3+/-7 min) (p < 0.01). Also, exercise time was longer in M + C and P + C compared with the P + P (115.1+/-7.6 min) (p < 0.01 and p < 0.05 respectively). These results indicate that the combination of a pre-exercise carbohydrate meal and a carbohydrate-electrolyte solution further improves endurance running capacity than the carbohydrate-electrolyte solution alone.